LITERATURE-BASED EFL INSTRUCTION: BENEFITS FOR LANGUAGE SKILLS DEVELOPMENT, LEARNING MOTIVATION, AND CULTURAL UNDERSTANDING - Mardiani, Mardiani; Baharuddin, Andi Farid (LLT Journal: A Journal on Language and Language Teaching, 2023)
In an EFL teaching context, the teacher's role is critical for helping students master four English skills. Teachers should ensure that the used learning tools can develop students’ language skills (in terms of listening, reading, speaking, and writing). According to experts, literature is a useful learning tool for achieving these objectives. Therefore, this article investigates the benefits of integrating literature into language learning activities. The research method used in this article is qualitative method with the library research approach. The data collected are separated into two types of data, i.e. primary and secondary. Both of these data sources are obtained from several articles (published in either national or international journals), books, and conference papers that relate to the use of literature in English teaching and learning. The total number of sources analyzed in the findings are 8 articles, 4 books, and 3 papers of conferences. The results show that using literature in language learning activities has various advantages, i.e., 1) developing the learners’ language skills, 2) triggering students’ learning motivation, 3and ) providing multi-cultural understanding for EFL learners.